Factors associated with breast-feeding initiation and continuation in Canadian-born and non-Canadian-born women: a multi-centre study. Issue 10 (3rd October 2022) - Chooniedass, Rishma; Tarrant, Marie; Turner, Sarah; Lok Fan, Heidi Sze; Del Buono, Katie; Masina, Stephanie; Becker, Allan B; Mandhane, Piushkumar; Turvey, Stuart E; Moraes, Theo; Sears, Malcolm R; Subbarao, Padmaja; et al.
Abstract: Objective: To identify factors associated with breast-feeding initiation and continuation in Canadian-born and non-Canadian-born women. Design: Prospective cohort of mothers and infants born from 2008 to 2012: the Canadian Healthy Infant Longitudinal Development (CHILD) Cohort Study. Setting: General community setting in four Canadian provinces. Participants: In total, 3455 pregnant women from Vancouver, Edmonton, Winnipeg and Toronto between 2008 and 2012. Results: Of 3010 participants included in the current study, the majority were Canadian-born (75·5 %). Breast-feeding initiation rates were high in both non-Canadian-born (95·5 %) and Canadian-born participants (92·7 %). The median breast-feeding duration was 10 months in Canadian-born participants and 11 months in non-Canadian-born participants. Among Canadian-born participants, factors associated with breast-feeding initiation and continuation were older maternal age, higher maternal education, living with their partner and recruitment site. Rooming-in during the hospital stay was also associated with higher rates of breast-feeding initiation, but not continuation at 6-month postpartum. Factors associated with non-initiation of breast-feeding and cessation at 6-month postpartum were maternal smoking, living with a current smoker, caesarean birth and early-term birth. Among non-Canadian-born participants, maternal smoking during pregnancy was associated with lower odds of breast-feeding initiation and lower odds of breast-feeding continuation at 6 months, and older maternal age and recruitment site were associated with breast-feeding continuation at 6 months. Conclusions: Although Canadian-born and non-Canadian-born women in the CHILD cohort have similar breast-feeding initiation rates, breast-feeding initiation and continuation are more strongly associated with socio-demographic characteristics in Canadian-born participants. Recruitment site was strongly associated with breast-feeding continuation in both groups and may indicate geographic disparities in breast-feeding rates nationally.